Poor clinical outcomes associated to multimorbidity, frailty and malnutrition in patients with atrial fibrillation - Eva Soler-Espejo; Beatriz Ángela Zazo-Luengo; José Miguel Rivera-Caravaca; Raquel López-Gávez; María Asunción Esteve-Pastor; Gregory Y.H. Lip; Francisco Marín; Vanessa Roldán (Elsevier, 2025)
Background: Atrial fibrillation (AF) patients often present with a higher prevalence of comorbidities, frailty, and malnutrition. We investigated if multimorbidity, frailty and malnutrition were associated with clinical outcomes in patients with AF starting vitamin K antagonist (VKA) therapy. Methods: Prospective observational cohort study including AF outpatients starting VKAs from July 2016 to June 2018. Multimorbidity was assessed by the number of comorbidities, frailty was evaluated using the Clinical Frailty Scale (CFS), and nutritional status was appraised using the Controlling Nutritional Status (CONUT). During 2-years of follow-up, ischemic strokes/transient ischemic attacks (TIA), major bleeds, and all-cause deaths, were recorded. Results: 1050 AF patients (51.4% female; median age 77 years, IQR 70-83) were included. Of these, 912 (86.9%) had multimorbidity (≥2 comorbidities additional to AF), 186 (17.7%) exhibited any frailty degree (CFS ≥ 5), and 76 (7.2%) had moderate-to-severe malnutrition (CONUT ≥ 5). The crude number of comorbidities and the CFS were significantly associated with major bleeds, whereas the CFS and the CONUT score were related to all-cause mortality. After adjustment, any frailty degree was associated with higher risks of major bleeding (aHR 3.04, 95% CI 1.67−5.52) and death (aHR 2.04, 95% CI 1.39−3.01). Moderate-to-severe malnutrition increased risk for ischemic stroke/TIA (aHR 2.25, 95% CI 1.11−4.56) and all-cause mortality (aHR 3.21, 95% CI 2.14−4.83). Conclusions: In this real-world prospective cohort of AF taking VKAs, most patients had multiple comorbidities, frailty and malnutrition. Frailty and malnutrition were important risk factors for bleeding, stroke, and mortality in these patients.